2023
DOI: 10.3168/jds.2022-22458
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cheese ripening by single-sided nuclear magnetic resonance

Abstract: The noninvasive, longitudinal study of products and food processing is of interest for the dairy industry. Here, we demonstrated that single-sided nuclear magnetic resonance (NMR) can be used for noninvasive monitoring of the cheese ripening process. The maturation of soft-ripened Camembert-like molded cheese samples was monitored for 20 d measuring 1-dimensional and 2-dimensional NMR relaxation and diffusion data at various depths, ranging from the hard surface layer to the soft center. Gelation and gel shrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Additionally, analysis of the relative peak integrals in the T 1 −T 2 maps revealed that protein and fat peaks increased proportionally with the ripening time, which is widely used in the food industry. 38−40 These peak assignments are in accord with findings from previous studies, 38,41,42 However, due to the ill-posed nature of ILT, the percentages of these components can only roughly reflect their relative proportions, making them unsuitable for precise quantification.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, analysis of the relative peak integrals in the T 1 −T 2 maps revealed that protein and fat peaks increased proportionally with the ripening time, which is widely used in the food industry. 38−40 These peak assignments are in accord with findings from previous studies, 38,41,42 However, due to the ill-posed nature of ILT, the percentages of these components can only roughly reflect their relative proportions, making them unsuitable for precise quantification.…”
Section: ■ Results and Discussionsupporting
confidence: 82%
“…Fourth, T 1 relaxation and T 2 relaxation (T 1 −T 2 ) correlation experimental data of cheese ripening: 38 three sets of 2D Laplace data were collected on the 10th, 15th, and 20th days of the cheese curing process, which was prepared from 400 mL of pasteurized milk with additives. Laplace NMR experiments were performed on a Magritek Profile NMR-Mouse PM 25 instrument with a 13.29 MHz 1 H resonance frequency and 7.28 T m −1 gradient, Kea 2 spectrometer, and Prospa software.…”
Section: ■ Experimentsmentioning
confidence: 99%
“…As these changes are best revealed by changes in T 1 , T 2 , and D , they can be tracked using ultrafast Laplace NMR in a way that traditional 2D NMR cannot. Examples include examining water movement in silica and cement, , the monitoring of cheese ripening, or monitoring the aggregation of ionic liquids. , Regardless of evident potential, these methods have not yet broadly been applied to studying chemical reactions, although there is one example using changes in T 2 and D to monitor binding of pyridine to an iridium catalyst and its metal-catalyzed deuteration (Figure d) …”
Section: Applying the Ultrafast Approach To Laplace Nmrmentioning
confidence: 99%
“…Such a feature has been widely utilized in the study of art artifacts, 15–19 medical materials, 20 car tires, 21 cartilage, 22,23 and skin 24 . In addition, the NMR‐MOUSE has also been widely utilized in studies where depth profiling is not measured, such as geopolymer curing, 25 archeology, 26,27 and food manufacturing and control 28–32 . Novel Ultra‐Fast Laplace NMR sequences are also feasible with NMR‐MOUSE, 33–36 which opens the possibility to study fast processes using single‐sided magnet.…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, the NMR-MOUSE has also been widely utilized in studies where depth profiling is not measured, such as geopolymer curing, 25 archeology, 26,27 and food manufacturing and control. [28][29][30][31][32] Novel Ultra-Fast Laplace NMR sequences are also feasible with NMR-MOUSE, [33][34][35][36] which opens the possibility to study fast processes using single-sided magnet.…”
mentioning
confidence: 99%